EFEKTIVITAS BUKU AKTIVITAS CODING UNPLUGGED DALAM MENGEMBANGKAN COMPUTATIONAL THINKING ANAK USIA DINI - NURHAMIDAH NASUTION (STKIP Subang, 2026)
Computational thinking is a foundational problem-solving competence that can be introduced in early childhood, yet digital devices are not always accessible or developmentally suitable. This study analyzes the effectiveness of an unplugged coding activity book as a screen-free medium for developing young children's computational thinking. An integrative review was conducted on peer-reviewed literature published mainly between 2019 and 2026 concerning unplugged programming, early coding, activity-based learning, and assessment for children aged three to eight. The synthesis shows that paper-and-pencil tasks, cards, tangible sequencing, stories, movement, and visual routes can strengthen sequencing, pattern recognition, algorithmic thinking, representation, decomposition, and debugging when activities are systematic and supported by teacher scaffolding. Activity books are promising because they organize gradual, repeatable, low-cost, and observable tasks. Their effectiveness depends on developmental suitability, clear visuals, opportunities for manipulation and discussion, sufficient duration, teacher knowledge, and valid assessment. They are best used as an introductory and complementary medium rather than a substitute for play, social interaction, or later plugged coding experiences.